A Comparative Study of Donald Trump’s Tariff Announcements under U.S. and Indonesian Capital Market Law - Hans, Stefanie; Sabini, Marianne Charleen (Anthology: Inside Intellectual Property Rights, 2025)
The capital market in Indonesia rests on the law No. 8 of 1995 on Capital Market, which is enforced by the Financial Services Authority (OJK). The said law contains provisions concerning market conduct and material information disclosure and imposes sanctions for any manipulation or misleading practice in the financial sector. The fact is, however, that the need and practice of the regulatory regime in Indonesia, as compared with that of the U.S., are increased in intensity with respect to such factors as political pronouncements which do not follow the traditional spectrum of sources for market disruption. This comparison of legal systems will give a timely and interesting historic perspective on how capital market laws react to high-profile political communication events. To assess how Trump's proclamations on tariffs would be accommodated under the respective underpinnings of Indonesian and American securities law is thus not only academically enriching but very important for cross-border investors, regulators, and policymakers navigating the increasingly complex politics-financial world intersection. The result is, Indonesian legal and institutional structures have yet to develop to the extent of being capable of controlling these types of incidents well. Capital Market Act No. 8 of 1995 establishes broad definitions of manipulation but regulatory agencies and courts have not yet established clearly defined guidelines regarding how political and public communications affect market behaviors. The Otoritas Jasa Keuangan (OJK) needs to issue clear guidelines on digital communication surveillance and real-time monitoring capabilities since these capabilities are now essential in detecting new types of manipulation. Indonesia needs to implement several steps that will enhance its ability to respond to political distortions in the market. The Indonesian courts and OJK need to build their approach to interpretation through the process of learning comparative legal systems. The U.S. SEC issued landmark decisions via SEC v. The Texas Gulf Sulphur Co. and Basic Inc. v. Levinson decisions are solid precedents to determine whether public releases contain material misstatements or manipulative data. These decisions highlight the significance of materiality as well as scienter (intent) and the trading obligations of individuals possessing non-public information.